Letramento em saúde bucal e sua relação com qualidade de vida relacionada à saúde bucal de gestantes - Araujo, Gabriela de (2023)
During pregnancy, there is a susceptibility to changes and alterations in the oral cavity due to a series of hormonal, psychological and behavioral changes. Among these changes are caries and gingivitis; conditions that impact on self-perception of oral health and Oral HealthRelated Quality of Life (OHRQoL). Oral Health Literacy (OHL) is a concept that has been investigated, especially in this group of individuals, as understanding and applying healthrelated information can help in the diagnosis and treatment of possible changes, in addition to increasing women's adherence to preventive actions and therapeutic regimens. In this context, the aim of this study is to investigate the OHL and its association with OHRQoL among pregnant women assisted in the public health service in the city of Santa Maria, southern Brazil. This study was a cross-sectional, with a sample of 520 pregnant women in the period from April to October 2022. Sociodemographic, economic, psychosocial and behavioral data were collected through structured questionnaires. The Oral Health Impact Profile (OHIP-14) questionnaire was used to estimate the OHRQoL. The level of OHL was measured using the Brazilian Rapid Estimate of Adult Literacy in Dentistry (Breald-30). Data regarding oral conditions were obtained through clinical examinations performed by previously trained and calibrated examiners. The main clinical variables to be considered were dental caries by Decayed, Missing, and Filled Surfaces index (DMFS) and periodontal conditions Community Periodontal Index (adapted CPI). Moreover to descriptive analysis, multilevel Poisson Regression models were used to verify the association of OHL and health determinants with OHRQoL among pregnant women. Household income (RR 0.89; 95% CI 0.82-0.97), education level (RR 0.76; 95% CI 0.71-0.81), dental attendance (RR 1.04; 95% CI 1.00-1.14), social support (RR 1.31; 95% CI 1.19-1.45), untreated dental caries (RR 1.41; 95% CI 1.33- 1.50), gingival bleeding (RR 1.26; 95% CI 1.17-1.35) and OHL (RR 1.14; 95% CI 1.07-1.22) were associated a high overall OHIP-14 scores. Pregnant women with low OHL had 14% prevalence to present a worse OHRQoL. OHL, socioeconomics, demographic, psychosocial, behavioral and clinical variables were associated a poorer OHRQoL among pregnant women assisted in public services.